2018
DOI: 10.1371/journal.pcbi.1006284
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the human erythrocyte Band 3 anion exchanger 1 (AE1, SLC4A1) with lipids and glycophorin A: Molecular organization of the Wright (Wr) blood group antigen

Abstract: The Band 3 (AE1, SLC4A1) membrane protein is found in red blood cells and in kidney where it functions as an electro-neutral chloride/bicarbonate exchanger. In this study, we have used molecular dynamics simulations to provide the first realistic model of the dimeric membrane domain of human Band 3 in an asymmetric lipid bilayer containing a full complement of phospholipids, including phosphatidylinositol 4,5–bisphosphate (PIP2) and cholesterol, and its partner membrane protein Glycophorin A (GPA). The simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 101 publications
9
50
1
2
Order By: Relevance
“…The coordinates of the mdAE1 (residues 382–887) were obtained from the crystal structure Protein Data Bank (PDB): 4YZF ( 7 , 37 ). The models were built without the inhibitor DIDS that is present in the crystal structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinates of the mdAE1 (residues 382–887) were obtained from the crystal structure Protein Data Bank (PDB): 4YZF ( 7 , 37 ). The models were built without the inhibitor DIDS that is present in the crystal structure.…”
Section: Methodsmentioning
confidence: 99%
“…To model the protein secondary and tertiary structure, an elastic network model with a cut-off distance of 7 Å was used. The elastic network model used in this study is a network that is fairly standard for simulations with the Martini force field, and it was used in a large number of studies that showed good agreement with experimental data, including our previous study on AE1 ( 37 , 44 ). The distance between the dimeric cytoplasmic and membrane domains is greater than the aforementioned 7 Å cut-off distance that was used for the elastic network model (∼24 and ∼20 Å for the rev-V and the V conformers, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…27) In DIDS-modified erythrocytes, the hypotonic hemolysis is enhanced, whereas the hemolysis at 200 MPa is suppressed. 26) Interestingly, in cholesterol-depleted erythrocytes that exhibit a decreased surface area-to-volume ratio, 28,29) hypotonic hemolysis 15) and pressure-induced one are enhanced. Taken together, the hypotonic hemolysis of erythrocytes is enhanced upon reduction of the surface area-to-volume ratio, whereas pressure-induced hemolysis is independent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of transporters are often complemented by MD simulations to gain insights into the dynamics of transporters. This dynamic is affected by oligomeric assemblies and how they perturb membrane properties in bilayers forming unique protein–lipid fingerprints [ 66 ]; those may also affect elevator movements [ 67 ].…”
Section: Structural Mechanisms Of Transporters Involved In B Toxicitymentioning
confidence: 99%